Infrastructure Readiness for Blended Learning in Vocational Higher Education: A Case Study from the Faculty of Engineering, Universitas Negeri Padang - Nelvi Salendra; M. Giatman; Nurhasan Syah; Aswardi (Universitas Negeri Padang, 2025)
The evolution of technology and the COVID-19 pandemic have accelerated the adoption of blended learning in higher education, including in vocational institutions. However, infrastructure readiness plays a pivotal role in the success of this implementation, especially in practice-based technical education. This study aims to assess the level of infrastructure readiness for supporting blended learning at the Faculty of Engineering, Universitas Negeri Padang, and to identify supporting and hindering factors. A quantitative descriptive survey method was used, with data collected through observations, interviews, and document analysis. The results showed that the infrastructure readiness level reached 65.11%, indicating moderate compliance with national standards as outlined in the Ministry of Education Regulation No. 3/2020. The main challenges identified include mismatches between equipment procurement and space availability, limited internet connectivity, and underutilized e-learning applications. Supporting factors included increased digital devices, provision of internet data for students and lecturers, and improvements in e-learning platforms. These findings highlight the need for continuous reinforcement of digital infrastructure to ensure the effectiveness of blended learning in the post-pandemic era.